First year engineering students: Perceptions of engineers and engineering work amongst local and international students - Bennett, Dawn; Kapoor, Ranjna; Attar Singh, Rajinder Kaur; Maynard, Nicoleta (The International Journal of the First Year in Higher Education, 2015)
Despite being well ahead of many other disciplines in establishing strong and evidence-based research and practice, engineering in many countries still experiences high rates of student and graduate attrition. One possible reason for this is that students enter engineering study without understanding the realities of either their degree program or engineering work, and without a sense of motivation and commitment. The research reported here aimed to extend understanding of first year engineering students’ thinking about their competencies, identity, self-efficacy, motivation, and career. The study involved over 1,100 first year engineering students enrolled in a common first year unit. Responses were coded using the Engineers Australia graduate competencies as a framework, and this paper reports findings from the most diverse cohort of students (n=260), of whom 49% were international students with English as their second language. The research identified differences between international and domestic students’ perceptions of self and of career competencies, possibly related to self-esteem. Implications include improved confidence and motivation to learn as students consider their strengths, interests and goals. Further, the research raises the need for analysis of international students’ cultural and educational background to determine how different cohorts of international students self-appraise and how they associate learning with their future careers.